Peran Kiai Sebagai Inisiator dan Elitist Charismatic dalam Membentuk Akuntabilitas Nahdlatul Ulama - Novi Wulandari (Universitas Negeri Malang, 2019)
Abstract: Nahdlatul Ulama (NU) is a religious organization that has a representative from traditional ulama with the ideology of ahlus sunnah waljamaah. Along with its development, NU still holds a culture that is derived from its predecessors (Kiai) in managing the organization, both in the organizational structure and in terms of organizing community-based non-profit organizations that have a principle of accountability. For this reason, the purpose of this research is to analyze and describe the reality of the role of the Kiai in forming NU’s accountability. The research perspective used is the interpretive paradigm with qualitative research methods through a multiple case study approach. The results of the study revealed that the role of the Kiai as an initiator in establishing accountability was shown by the provision of ideas in accordance to the needs of NU residents in particular, and the Indonesian State in general. This role can be categorized as the Elitist-charismatic values — which is the value system of pride of the charismatic leader which results in the fanaticism of the members of the organization. Since the charismatic nature of the kiai is temporary, these values are transitional. NU's accountability process is called